2020
DOI: 10.3390/jcm9041200
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs in Biliary Tract Cancer—An Up-to-Date Review

Abstract: The term long non-coding RNA (lncRNA) describes non protein-coding transcripts with a length greater than 200 base pairs. The ongoing discovery, characterization and functional categorization of lncRNAs has led to a better understanding of the involvement of lncRNAs in diverse biological and pathological processes including cancer. Aberrant expression of specific lncRNA species was demonstrated in various cancer types and associated with unfavorable clinical characteristics. Recent studies suggest that lncRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 249 publications
(340 reference statements)
0
5
0
Order By: Relevance
“…Although these studies have revealed important findings, they also have limitations. First, we still lack a comprehensive understanding of the regulation of a single lncRNA because the mechanism of ceRNA is only one of its many modes of action ( 11 , 34 ). Most tumors occur due to the cumulative mutation of multiple genes and complex processes involving many signal transduction pathways ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies have revealed important findings, they also have limitations. First, we still lack a comprehensive understanding of the regulation of a single lncRNA because the mechanism of ceRNA is only one of its many modes of action ( 11 , 34 ). Most tumors occur due to the cumulative mutation of multiple genes and complex processes involving many signal transduction pathways ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are non‐coding RNAs without open reading frame (ORF) and are usually spliced and polyadenylated 10 . Different subtypes of lncRNAs participate in modulating protein‐coding genes, but the specific molecular mechanisms are varied 11–13 . Among the regulatory mechanisms, competitive endogenous RNA (ceRNA) mechanism has attracted widespread attention.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Different subtypes of lncRNAs participate in modulating protein‐coding genes, but the specific molecular mechanisms are varied. 11 , 12 , 13 Among the regulatory mechanisms, competitive endogenous RNA (ceRNA) mechanism has attracted widespread attention. lncRNA and miRNA might be a key in regulating of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…On a molecular level, BTCs harbor a complex landscape of genetic aberrations which affects, among others, cell cycle regulation, signal transduction and apoptosis response [2]. Moreover, it is well established that several epigenetic mechanisms are deregulated in BTC, including DNA methylation, histone modifications and expression of non-coding RNAs [2,[4][5][6][7][8]. As symptoms are rather unspecific, most patients are diagnosed at an already advanced stage of the disease, hence, therapeutic options are limited and the five-year survival rate remains poor [1].…”
Section: Introductionmentioning
confidence: 99%